Evaluation of clinical efficacy of Cention N and Tetric N-ceram in class I carious lesion in primary mandibular molars - Mayur Mhole; Sandeep Tandon; Shriya Gupta; Harshita Gosavi; A. Rizwan Ali; Mineet Kaul (Journal of Oral Biology and Craniofacial Research)
Background: Tetric N-Ceram, recently introduced as an alternative to bulk-fill flowable and traditional non-flowable composite. Cention N, recently introduced tooth-coloured filling material for bulk placement in retentive preparations. Aim: The aim of the present study is to evaluate the performance of Tetric N Ceram and Cention N as restorative materials in Class 1 carious lesions in primary mandibular molars. Design: A prospective double-blind, split-mouth, parallel-group, randomized study was conducted on 34 patients having bilateral Class I carious lesions on mandibular primary molars. 68 teeth were divided into 2 groups: Group 1 was treated with Cention N and Group 2 with Tetric N Ceram. All restorations were clinically evaluated at Baseline – 24hrs, 3, 6 and 9 months for marginal integrity (MI), secondary caries(SC) and gross fracture(GF) using the US Public Health Service criteria (modified Ryge criteria). For post-operative sensitivity(POS), Wong Bakers faces pain rating scale was used. Results: Intragroup comparison of MI, SC and GF in Group 1 and group 2 showed non-significant difference at all-time intervals. Intergroup comparison showed non-significant difference for MI, SC, GF and POS at all-time intervals. Conclusion: Tetric N Ceram and Cention N in terms of MI, SC, GF and POS provide similar results.